A Differentiation-Based Brand Image Strategy to Increase the Number of Non-BPJS Patients at A Private Hospital in Jember - Annisa Camalia Anjani; Bambang Iskandriawan (Green Publisher Indonesia, 2026)
Private hospitals in Indonesia face a dual challenge: serving a high proportion of BPJS patients while maintaining organizational sustainability through services for non-BPJS patients. However, negative public perceptions of the BPJS system may affect a hospital's brand image and obscure its differentiation in the minds of consumers. This study formulates a differentiation-based brand image strategy to increase non-BPJS patient utilization at Private Hospital X in Jember—a Type C hospital with approximately 80% of its patients covered by BPJS—using the Double Diamond Design Thinking framework. Employing a qualitative case study approach, data were collected from internal stakeholders through in-depth interviews, digital observation, and document analysis. Thematic analysis identified key themes related to determinants of hospital selection, internal challenges in brand image management, and potential differentiation strategies. Strategic recommendations were developed through market segmentation, the formulation of Points-of-Parity (POP) and Points-of-Difference (POD), a desired brand image framework, and the implementation of the 7Ps Marketing Mix. The findings reveal that non-BPJS patients are predominantly price-sensitive consumers who prioritize value for money, while the hospital's internal challenges include limited human resource competencies and an unstructured branding system. The study concludes that Hospital X possesses strong functional and symbolic advantages, including humanistic service, affordable pricing, and a wide range of non-BPJS services, but requires a more strategic communication approach to strengthen its differentiation. This research contributes an applied strategic framework to support managerial decision-making for the development of non-BPJS services within the field of Strategic Brand Management.